Measuring Service Quality Of Public Hospitals - Damodaran, Yadu K; Mani, Kannan a/I; Muhammad, Ali; Saleem, Muhammad Saad (Journal of Mental Health and Social Rehabilitation, 2023)
In public hospitals the services quality has become an imperative in providing satisfaction because delivering services quality directly affected the patients’ perception. The public sector should ensure patients receive the best services in hospitals. Though there has been an attempt to improve the situation it seems not much has been achieved in raising the quality of service in public sector and this is compounded by limited information on the factors that ail the delivery of service quality in the public hospital. Therefore, this research was conducted to know perception of patients about the services quality of public hospital in Lahore Pakistan. The study used a descriptive survey approach in collecting data from the respondents. The number of the respondents was 100 and the respondent was patients. Through convenient sampling the data is collected. A questionnaire was used to collect the data from primary sources. Quantitative technique was used to analyzed the data. For this purpose, ‘SERVQUAL’ instrument was used to measure the service quality delivered by the hospital. Findings show that all the factors discussed in the thesis affect the patients’ perception but the result of infrastructure is the highest which means that infrastructure of the hospitals are positively associated with the perception of patients, but management of hospitals need to work on trustworthiness because of negative perception of patients